Development of Pre-Anesthesia Documentation in Electronic Medical Record Anesthesia (AREME) - Try Budi Wilogo; Marta Tania Gabriel Ching Cing; Heru Purnawan Jati Wibowo; Rully Annisa (Jurnal Ilmiah Multidisiplin, 2026)
Anesthesia Care Nursing Documentation (ASKAN) is a record that contains the actions performed by an anesthesiologist on a patient. In the existing Electronic Medical Record Anesthesia (AREME) application, documentation is limited to intra-anesthesia. This does not align with the guidelines in the Anesthesia Care Nursing Documentation (ASKAN) manual. This study aims to develop the AREME application by adding pre-anesthesia documentation, in accordance with the guidelines outlined in the ASKAN manual. The research method used is Research and Development (R&D) with the Waterfall software development method, which includes the stages of Requirement, Design, Implementation, Verification, and Maintenance. The results of this study produced a new interface and pre-anesthesia documentation in the AREME application, in accordance with the guidelines in the ASKAN manual. System testing was conducted using Black Box Testing with Use Case testing techniques, and the results showed that all system functions operate according to the specified requirements. Therefore, this study successfully developed pre-anesthesia documentation in the web-based Electronic Medical Record Anesthesia (AREME) application.